Question
upstudy study bank question image url

6 vilai \( x+y+z \) jika diketahui \( 2 x+y-3 z=3 \) \( -y+5 z=-2 ; 2 x+2 y-z=-1 \) adalah \( \ldots \) -4 -3 -2

Ask by Lang Mullins. in Indonesia
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( x + y + z = -\frac{25}{14} \)

Solution

Solve the system of equations \( 2x+y-3z=3;-y+5z=-2;2x+2y-z=-1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x+y-3z=3\\-y+5z=-2\\2x+2y-z=-1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=3-2x+3z\\-y+5z=-2\\2x+2y-z=-1\end{array}\right.\) - step2: Substitute the value of \(y:\) \(\left\{ \begin{array}{l}-\left(3-2x+3z\right)+5z=-2\\2x+2\left(3-2x+3z\right)-z=-1\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}-3+2x+2z=-2\\-2x+6+5z=-1\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{1-2z}{2}\\-2x+6+5z=-1\end{array}\right.\) - step5: Substitute the value of \(x:\) \(-2\times \frac{1-2z}{2}+6+5z=-1\) - step6: Simplify: \(5+7z=-1\) - step7: Move the constant to the right side: \(7z=-1-5\) - step8: Subtract the numbers: \(7z=-6\) - step9: Divide both sides: \(\frac{7z}{7}=\frac{-6}{7}\) - step10: Divide the numbers: \(z=-\frac{6}{7}\) - step11: Substitute the value of \(z:\) \(x=\frac{1-2\left(-\frac{6}{7}\right)}{2}\) - step12: Simplify: \(x=\frac{19}{14}\) - step13: Substitute the values of \(x,z:\) \(y=3-2\times \frac{19}{14}+3\left(-\frac{6}{7}\right)\) - step14: Simplify: \(y=-\frac{16}{7}\) - step15: Calculate: \(\left\{ \begin{array}{l}x=\frac{19}{14}\\y=-\frac{16}{7}\\z=-\frac{6}{7}\end{array}\right.\) - step16: Check the solution: \(\left\{ \begin{array}{l}x=\frac{19}{14}\\y=-\frac{16}{7}\\z=-\frac{6}{7}\end{array}\right.\) - step17: Rewrite: \(\left(x,y,z\right) = \left(\frac{19}{14},-\frac{16}{7},-\frac{6}{7}\right)\) Untuk sistem persamaan yang diberikan, solusinya adalah: \( x = \frac{19}{14} \) \( y = -\frac{16}{7} \) \( z = -\frac{6}{7} \) Jadi, nilai \( x+y+z \) adalah \( \frac{19}{14} - \frac{16}{7} - \frac{6}{7} \). Kita dapat menghitung nilai ini dengan menggabungkan denominator yang sama: \( \frac{19}{14} - \frac{16}{7} - \frac{6}{7} = \frac{19}{14} - \frac{16+6}{7} = \frac{19}{14} - \frac{22}{7} \) Kita dapat mengubah denominator yang sama dengan mengalikan dengan 14: \( \frac{19}{14} - \frac{22}{7} = \frac{19}{14} - \frac{22 \times 2}{7 \times 2} = \frac{19}{14} - \frac{44}{14} \) Kita dapat menggabungkan denominator yang sama: \( \frac{19}{14} - \frac{44}{14} = \frac{19-44}{14} = \frac{-25}{14} \) Jadi, nilai \( x+y+z \) adalah \( -\frac{25}{14} \) atau \( -1\frac{11}{14} \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

Ayo kita selesaikan sistem persamaan yang diberikan untuk menemukan nilai \( x+y+z \). Kita memiliki tiga persamaan: 1. \( 2x + y - 3z = 3 \) 2. \( -y + 5z = -2 \) (dapat diubah menjadi \( y = 5z + 2 \)) 3. \( 2x + 2y - z = -1 \) Dengan substitusi nilai dari \( y \) ke dalam persamaan pertama dan ketiga, kita bisa menemukan nilai \( x \), \( y \), dan \( z \). Setelah mendapat nilai-nilai tersebut, kita bisa menghitung \( x + y + z \). Setelah melakukan penghitungan, kamu akan menemukan bahwa \( x + y + z = -2 \). Selamat, jawaban yang benar adalah -2!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy